Employee Well-being as mediator of correlation between Psychological Capital and Psychological Climate - Laila Meiliyandrie Indah Wardani; Tesya Noviyani (Journal of Educational, Health and Community Psychology, 2020)
Individual differences are one of the factors that influence the psychological climate. The existence of bias and the existence of the perception of the influence of other factors on an individual, so that in the same neighborhood but in different individuals our own ingrained perceptions would be different. It affects individual’s self-efficacy as one of dimension on psychological capital, psychological capital associated with a person's perception of well-being of employees or referred to as employee well-being, where the employee well-being as well as a factors effect of psychological climate. Therefore, this study aims to determine whether employee well-being as a mediator of the relationship between psychological capital and psychological climate of hospitality employees. Respondents were 378 hospitality employees, the analysis used regression analysis model 4 v3.0 mediation process by Hayes. The results showed that employee well-being acts as a partial mediator in the relationship between psychological capital and psychological climate, so that with the existence of employee well-being the relationship between psychological capital and psychological climate will be greater. Research found that the contribution dimension to psychological climate has the greatest relationship with the dimension of psychological well-being in employee well-being, other than that there were differences in employee well-being in the age range of 18-30 years with ages 31-60 years and also differences in psychological climate in the age range from 18-30 years with ages 31-60 years.